A pesquisa na formação de professores do curso de pedagogia na Unesp Bauru: análise dos Trabalhos de Conclusão de Curso 2005-2015 - Franco, Ana Beatriz Momesso [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The present work of course conclusion arose before the process of articulation and curricular restructuring of the Pedagogy courses carried out at the request of the Graduate Rectorate of UNESP, with the objective of triggering actions that lead to the constitution of similar curricular organizations for the courses of same nomenclature. The documents studied preliminarily pointed out that, although all courses comply with the same legislation, the curricular organization of each one presents singularities. So, we asked: What were the themes for the development of the Works of Completion of Course in Pedagogy of UNESP of Bauru? How are these subjects related to the course subjects? What is the contribution of this initiation to scientific research in the formation of the future Pedagogue? These and other issues have emerged, since not all UNESP Pedagogy courses present in their curricular structure the obligation to present the Course Completion Work. In this way, the general objective of the research was to know and analyze the Completion Works of Pedagogy Course of UNESP of Bauru during 10 years (2005-2015) of. There were therefore stages of the work: 1) review of the literature on the initiation of scientific research in teacher training; 2) study of the official documents of the course of Pedagogy of UNESP of Bauru; 3) survey of the Completion Works presented between 2005 and 2015; 4) organization of the categories of analysis; 5) description and categorization of data; 6) analysis and interpretation of results. We believe that studies of this nature contribute to the reflection of the necessary articulation about the research in the initial formation of teachers in the context of the contemporary school.

O presente trabalho de conclusão de curso surgiu diante do processo de articulação e reestruturação curricular dos cursos de Pedagogia realizado a pedido da Pró-Reitoria de Graduação da UNESP, com o objetivo de desencadear ações que levem à constituição de organizações curriculares semelhantes para os cursos de mesma nomenclatura. Os documentos estudados preliminarmente apontaram que, embora todos os cursos obedeçam a mesma legislação, a organização curricular de cada um apresenta singularidades. Assim, indagamos: Quais foram os temas para o desenvolvimento dos Trabalhos de Conclusão de Curso na Pedagogia da UNESP de Bauru? Como essas temáticas estão relacionadas com as disciplinas do curso? Qual a contribuição dessa iniciação à pesquisa científica na formação do futuro Pedagogo? Essas e outras questões emergiram, pois nem todos os cursos de Pedagogia da UNESP apresentam na sua estrutura curricular a obrigatoriedade da apresentação do Trabalho de Conclusão de Curso. Desta forma, o objetivo geral da pesquisa foi conhecer e analisar os Trabalhos de Conclusão de Curso de Pedagogia da UNESP de Bauru durante 10 anos (2005-2015) de. Foram, portanto, etapas do trabalho: 1) revisão da literatura sobre a iniciação à pesquisa científica na formação de professores; 2) estudo dos documentos oficiais do curso de Pedagogia da UNESP de Bauru; 3) levantamento dos Trabalhos de Conclusão de Curso apresentados entre 2005 e 2015; 4) organização das categorias de análise; 5) descrição e categorização dos dados; 6) análise e interpretação dos resultados. Acreditamos que estudos dessa natureza contribuem para reflexão da articulação necessária sobre a pesquisa na formação inicial de professores no contexto da escola contemporânea.
Keywords: Professores - Formação; Licenciatura; Educação; Education